Intraosseous angioleiomyoma of the mandible- Report of a rare case - K.S. Gamal Abdul Nasser; S.G. Wasim Ahamed; Madhu Narayan (Oral Oncology Reports)
Leiomyoma (LM) is a smooth muscle tumor of a benign nature frequent in the genital tract of females. It is infrequent in the oral cavity. Oral LMs are generally of the angioleiomyoma (ALM) type. In this article, we present a rare case of oral ALM in a 24-year-old male who had a painless swelling in the mandibular left buccal vestibule. Radiographically, there was the presence of left buccal cortical expansion. A tentative diagnosis of traumatic bone cyst/aneurysmal bone cyst was given. The microscopy of incisional biopsy revealed loose fibrovascular stroma and wavy spindle-shaped cells suggestive of a spindle cell neoplasm with features of neurofibroma. On immunohistochemical analysis, it was S100 negative but smooth muscle actin positive which led to the histopathological diagnosis of “LM.” The microscopic picture of the excised specimen showed spindle cells in an amorphous eosinophilic stroma, spicules of vital bone, dilated capillaries, and extravasated red blood cells. A final diagnosis of “ALM” was made. A local surgical excision was done. The follow-up of the patient was uneventful and there has been no recurrence to date. The intraosseous variety of LM, though a remote possibility, must be considered a differential diagnosis for central lesions of the mandible.